The Effects of Incremental Housing Approach on the Level of Residential Satisfaction - Mohammadhossein Azizibabani; Mohammadreza Bemanian (Iconarp International Journal of Architecture and Planning, 2019)
Housing has always been regarded as one of the basic human needs and initial rights and its related costs contain a significant portion of the household's income. Providing affordable housing for low-income groups in many countries, including Iran, is the task of the government and other supportive institutions. In this regard, the Iran’s government recently actions have more focused on the quantitative dimensions of housing production and qualitative issues, which are the main factors of residential satisfaction have less been considered. This paper investigates the effects of the incremental housing approach on the level of residential satisfaction in affordable housing projects. The research method is descriptive-analytic and data were collected through the case study. The results show that influenced indicators by the incremental housing approach including land and building ownership, providing technical and spatial basis for future development, quality improvement, and strengthen the social interactions among the residents, beside site design related indicators, including anticipation of the neighborhood units with proper pattern of activities are the most important factors of residential satisfaction. High residential satisfaction lead to bring a sense of belonging to the place and in upper level the social sustainability in the residential environment. Therefore, in order to increase the efficiency of the positive aspects of this approach, a model for determining the stages of work and necessary actions has been designed.